Extensive retroperitoneal hematoma after laparoscopic appendectomy - AlRumaih, Abdullah; Alzakari, Abdulmohsen; Alkhaibary, Ali; Alghanim, Fahad (International Surgery Journal, 2018)
The retroperitoneum is the abdominal portion located behind the sac of the peritoneal cavity and extending from the diaphragm to the pelvic inlet. A Retroperitoneal hematoma is a rare but a fearsome complication after appendectomy. The management of retroperitoneal hematomas can be difficult as the decision between a surgical intervention, angiographic embolization, and conservative management with fluids can be difficult to make. This case report would be outlining the clinical presentation, radiological findings, and outcome of a 60-year-old male who has been diagnosed with an intra-abdominal, retroperitoneal hematoma and flank ecchymosis with no signs of active bleeding after laparoscopic appendectomy. Retroperitoneal hematomas can be extensive post-laparoscopic abdominal surgeries. A comprehensive physical examination, radiological imaging, and laboratory investigations should be considered to rule out the possibilities of bleeding disorders and/or active bleeding contributing to the development of retroperitoneal hematomas.